The Effect Of Warm Water Foot Soak Therapy With Salt, Lemongrass And Ar-Rahman Murottal On Blood Pressure In Hypertension Sufferes - Nursyachlina, Icha Linda; Pramestirini, Rizky Asta; Faridah, Virgianti Nur (Media Keperawatan Indonesia, 2025)
Modern lifestyles often encourage frequent consumption of fast food and reduced physical activity, both of which contribute to the development of various diseases, including hypertension. This study aims to analyze the effect of warm water foot soak therapy with salt, lemongrass, and Ar-Rahman murottal on blood pressure in hypertension sufferers. The research adopts a pre-experimental design with a one-group pretest-posttest approach. The study population consisted of 45 respondents, with 41 participants selected through simple random sampling. This therapy was administered three times per week for 12 minutes per session. Research instruments included a sphygmomanometer, observation sheets, and standard operating procedures (SOP). Data were subjected to normality testing, and as they were not normally distributed, they were analyzed using the Wilcoxon test. The results indicate that, prior to intervention, 70.7% of respondents experienced Stage 2 hypertension, while 29.3% had Stage 1 hypertension. Post-intervention, 56.1% of respondents exhibited Stage 1 hypertension, and 7.3% achieved normal blood pressure. The statistical analysis yielded a significant p-value of 0.000 (p < 0.05), confirming the effectiveness of this therapy in lowering blood pressure among hypertensive patients. The warm saltwater and lemongrass foot soak promoted vasodilation, improving blood circulation, while the murottal of Surah Ar-Rahman provided a calming and relaxing effect, positively influencing physiological responses and contributing to blood pressure reduction.